Syria in The Byzantine Age between the 4th century and the 7th century AD. (The development of Byzantine studies historical and archaeological). (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The Byzantine Empire was the legitimate heir of the Roman Empire in the West, especially after the fall of Rome in the 5th century AD by the Barbarians. Byzantine history continued for nearly a thousand years, in which Greek traditions and Christianity lived side by side. Byzantium was the imperial capital and the provinces, especially the eastern provinces such as Syria, belonged to it. This province played a major role in the Byzantine event and on many levels. The study includes the study of the stages of the development of Byzantine history academically through ancient Byzantine historical sources and studies and research carried out by universities in Europe as a framework for Byzantine studies as well as archaeological excavations that took place in the last century throughout the empire. The research will also shed light on the historical and archaeological information contained in sources and references about Syria as the most important eastern states in the empire. It reviews the most important centers of Byzantine historical and archaeological heritage in Syria between the fourth century and the seventh century. The research attempts to help Arab specialists and researchers in Byzantine history to gain knowledge of the historical and archaeological structure of historical sources and references of Byzantine studies. كانت الإمبراطورية البيزنطية الوريث الشرعي للإمبراطورية الرومانية في الغرب، وخصوصاً بعد سقوط العاصمة روما في القرن الخامس الميلادي بيد البرابرة. استمر التاريخ البيزنطي فيما بعد قُرابة الألف عام، عاشت فيها التقاليد اليونانية والديانة المسيحية جنباً إلى جنب. كانت بيزنطة العاصمة الإمبراطورية وكانت الولايات وخصوصاً الولايات الشرقية كسوريا تتبع لها. لعبت ولاية سوريا دوراً كبيراً في الحدث البيزنطي وعلى مستويات عديدة. يتضمن البحث دراسة مراحل تطور التاريخ البيزنطي أكاديمياً من خلال المصادر التاريخية البيزنطية القديمة والدراسات والأبحاث الحديثة نسبياً التي قامت بها الجامعات في أوروبا كإطار جامع للدراسات البيزنطية متضمنةً التنقيبات الأثرية التي جرت في القرن الماضي في أنحاء الإمبراطورية. سيُلقي المقال أيضاً الضوء على نوعية المعلومات التاريخية والأثرية الواردة في المصادر والمراجع عن سوريا كونها أهم الولايات الشرقية في الإمبراطورية. ويستعرض محطات من أهم مراكز الإرث التاريخي والأثري البيزنطي في سوريا بين القرن الرابع الميلادي والقرن السابع الميلادي. يُحاول البحث مُساعدة المختصين والباحثين العرب في التاريخ البيزنطي للإلمام بالهيكل العلمي التاريخي والأثري للمصادر والمراجع التاريخية للدراسات البيزنطية.